Synthesis of carbazoles by intramolecular arylation of diarylamide anions - Buden, Maria Eugenia (2009)
The synthesis of a series of substituted 9H-carbazoles by the photostimulated SRN1 substitution reactionwith diarylamines as starting substrate was performed. The diarylamines were obtained by two approaches,the Pd-catalyzed reactions (Buchwald-Hartwig) or Cu-catalyzed reactions of 2-haloanilines with aryl halides, or 2-bromoiodobenzene with anilines, with moderate to very good isolated yields (45-89%).Through an intramolecular C-C bond formation of diarylamines by the SRN1 mechanism, Carbazoles were achieved. These reactions proceeded synthetically in very good to excellent yields (81-99%) in liquid ammonia and DMSO. The reaction of N-(2-bromophenyl)-2-phenylbenzenamine gave 1-phenyl-9H-carbazole (38%) and the isomer 9H-tribenz[b,d,f]azepine (58%). By using this methodology, 9Hcarbazoles, substituted 9H-carbazoles, benzocarbazoles, and even 3,3′-bi(9H-carbazole) were obtained by a double SRN1 reaction with benzidine.